2019
DOI: 10.1186/s12974-019-1566-5
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus encephalitis in immunocompetent mice is dominated by innate immune cells and does not require T or B cells

Abstract: Background Until the end of the twentieth century, Zika virus (ZIKV) was thought to cause a mostly mild, self-limiting disease in humans. However, as the geographic distribution of ZIKV has shifted, so too has its pathogenicity. Modern-day ZIKV infection is now known to cause encephalitis, acute disseminated encephalomyelitis, and Guillain-Barré syndrome in otherwise healthy adults. Nevertheless, the underlying pathogenetic mechanisms responsible for this shift in virulence remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
5
26
0
Order By: Relevance
“…For example, in IFNAR −/− mice ZIKV infection of astrocytes results in a breakdown of the blood-brain barrier, allowing an influx of CD8+ T cells into the central nervous system (CNS) where they mediate apoptosis of ZIKV-infected neurons, but also results in severe neuropathology (87). Similarly, CD8+ cellular infiltration was also found in the CNS following ZIKV infection in C57/BL6 neonatal mice who developed hind limb collapse, cerebellar degeneration (88) and in the case of adult wildtype C57BL/6 mice, encephalitis (89). Whilst the CD8+ T cell response may be detrimental in the CNS, in IFNAR −/− pregnant mice cross-reactive DENV-specific CD8+ cells are protective against ZIKV infection of the fetus, including the fetal central nervous system, and are associated with increased fetal growth and viability (90).…”
Section: T Cell Responses In Mice and Non-human Primates (Nhp)mentioning
confidence: 99%
“…For example, in IFNAR −/− mice ZIKV infection of astrocytes results in a breakdown of the blood-brain barrier, allowing an influx of CD8+ T cells into the central nervous system (CNS) where they mediate apoptosis of ZIKV-infected neurons, but also results in severe neuropathology (87). Similarly, CD8+ cellular infiltration was also found in the CNS following ZIKV infection in C57/BL6 neonatal mice who developed hind limb collapse, cerebellar degeneration (88) and in the case of adult wildtype C57BL/6 mice, encephalitis (89). Whilst the CD8+ T cell response may be detrimental in the CNS, in IFNAR −/− pregnant mice cross-reactive DENV-specific CD8+ cells are protective against ZIKV infection of the fetus, including the fetal central nervous system, and are associated with increased fetal growth and viability (90).…”
Section: T Cell Responses In Mice and Non-human Primates (Nhp)mentioning
confidence: 99%
“…Encephalitis (inflammation of the brain), meningitis (Inflammation of membrane covering the brain), and myelitis (inflammation of spinal cord) are known to cause seizures. ZIKV infection causes encephalitis ( Hayashida et al, 2019 ). We thought that CST, with its anti-viral and anti-inflammatory activity, can be useful in reducing the seizure-related neuronal disorders apart from viral load reduction and, thus, the severity of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the notion of the protective role of IFN-I, studies conducted in Zika virus-induced encephalitis in mouse brain showed that IFN-I is insufficient to prevent the establishment of infection in mouse brain through innate immune response, rather adaptive response plays a major role in immunopathology [28]. Apart from innate responses to the pathogens, IFN-I plays an essential role in the development of CNS.…”
Section: Introductionmentioning
confidence: 89%